Pelatihan Peningkatan Ketrampilan Penyusunan Laporan Keuangan Untuk Koperasi Serba Usaha (KSU) SEMESTA - Suripto, Suripto; Prasetya, Victor; Hartoyo, Hartoyo (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
The purpose of the Community Service activity is to increase the knowledge and understanding of the management and members of the Koperasi Serba Usaha (KSU)